Speaker verification based on speech signal - Shariffah Fauziah, Jap; Chekima, Ali; Mazlina, Mamat; Wan Mahani, Abdullah (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.